Resting-State Cerebello-Cortical Dysfunction in Parkinson's Disease - Palmer, William C.; Cholerton, Brenna A.; Zabetian, Cyrus P.; Montine, Thomas J.; Grabowski, Thomas J.; Rane, Swati (Frontiers in Neurology, 2021)
Purpose: Recently, the cerebellum’s role in Parkinson’s disease (PD) has been highlighted. Therefore, this study sought to test the hypothesis that functional connectivity (FC) between cerebellar and cortical nodes of the resting-state networks differentiates Parkinson’s disease (PD) patients from controls by scanning participants at rest using functional magnetic resonance imaging (fMRI) and investigating connectivity of the cerebellar nodes of the resting-state networks. Materials and Methods: Sixty-two PD participants off medication for at least 12 hours and 33 controls (NC) were scanned at rest using blood oxygenation level dependent fMRI scans. Motor and cognitive function were assessed with the Movement Disorder Society’s revision of the Unified Parkinson’s Disease Rating Scale III and Montreal Cognitive Assessment, respectively. Connectivity was investigated with cerebellar seeds defined by Buckner’s 7-network atlas. Results: PD participants had significant differences in FC when compared to NC participants. Most notably, PD patients had higher FC between cerebellar nodes of the somatomotor network (SMN) and the corresponding cortical nodes. Cognitive functioning was differentially associated with connectivity of the cerebellar SMN and dorsal attention network. Further, cerebellar connectivity of frontoparietal and default mode networks correlated with severity of motor function. Conclusion: Our study demonstrates altered cerebello-cortical FC in PD, as well as an association of this FC with PD-related motor and cognitive disruptions, thus providing additional evidence for the cerebellum’s role in PD.